DOES THE TYPE OF INSULIN REGIMEN MATTERS TO AFFECT ADHERENCE AND GLYCEMIC PROFILE IN DIABETIC PATIENTS? - Hassan, Gul; Shabbir, Muhammad; Usman, Khalid; Sajjad, Muhammad Mohsin; Sajjad, Hassan (Journal of Postgraduate Medical Institute, 2019)
Objective: To determine level of adherence to different insulin regimens, its effect on glycemic profile and to find out reasons leading to non adherence. Methodology: This cross sectional study was conducted at the Department of Endocrinology, Hayatabad Medical Complex, Peshawar, from February 2016 to December 2016. Two hundred patients; 148 on basal bolus and 52 on premix insulin regimen were assessed. Adherence status was determined using Morisky medication adherence scale (MMAS=0). Fasting and random glucose levels were also recorded. After stratification into different groups, chi square test was applied while mean fasting glucose levels were compared using independent samples t test. Results: Overall adherence to insulin treatment was only 26.5%. Only 10% patients were highly adherent to treatment (MMAS=0). Only 33% patients had their fasting sugar in reasonable range (<140mg/dl). Among 148 patients on basal bolus regimen, only 15.5% were adherent to treatment while adherence to premix insulin was 57.7%. Fasting sugar levels were much better in premix group vs. basal bolus group (p value <0.05). Non-affordability was the main constraint responsible for non-adherence (54%). Conclusion: Adherence to insulin treatment than insulin type was more important in improving diabetes care. Premix insulin was a reasonable alternative to achieve glycemic control as the cost of drug remains main reason for non adherence.